AVLONIY ASARLARI – PEDAGOGLARGA DASTURIL AMAL YOHUD TA'LIM-TARBIYANING O'RNI (Archive of Conferences, 2022)
The extent to which society has risen has always depended on the educational upbringing of the younger generation. And the role of the teacher in the formation of education is invaluable. In his works, Abdullah Avloni pays special attention to this issue and expresses his views on the role of teachers.